Polyvinyl alcohol reinforced cross-linked gelatin composite active film and preparation method thereof

By adding polyvinyl alcohol (PVA) to the crosslinked gelatin composite film, the problem of poor mechanical properties and gas barrier properties is solved, and higher thermal stability, gas barrier properties and oxidation resistance are achieved, which enhances its application potential in the field of food packaging.

CN116769321BActive Publication Date: 2025-04-29HUNAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310847226.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-04-29
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

The mechanical properties and gas barrier properties of the existing crosslinked gelatin composite active films are not ideal, which limits its practical application in the field of food packaging.

Method used

The toughness and oxygen barrier properties of glucose crosslinked gelatin composite film are enhanced by adding polyvinyl alcohol (PVA) with high toughness, high transparency and good gas barrier properties.

Benefits of technology

The thermal stability, gas barrier properties and oxidation resistance of the crosslinked gelatin composite activated film are improved, and its application potential in the field of active packaging is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116769321B_ABST
    Figure CN116769321B_ABST
Patent Text Reader

Abstract

The present invention provides a polyvinyl alcohol reinforced cross-linked gelatin composite active film, wherein the polyvinyl alcohol reinforced cross-linked gelatin composite active film comprises gelatin, glycerol, glucose and polyvinyl alcohol (PVA). The present invention enhances the toughness and oxygen barrier properties of the glucose cross-linked gelatin composite film by adding PVA having high toughness, high transparency and good gas barrier properties. In addition, the present invention also relates to a preparation method of the polyvinyl alcohol reinforced cross-linked gelatin composite active film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a polyvinyl alcohol-reinforced cross-linked gelatin composite active film and a preparation method thereof. Background Art

[0002] Nowadays, plastic polymers are widely used in food packaging, but less than 5% of them are recyclable, which leads to huge environmental pollution. Natural biodegradable materials are considered as potential alternatives to common synthetic polymer materials because they are biodegradable, biocompatible, safe and multifunctional. The most widely used materials include polysaccharides, proteins and lipids. Among them, gelatin is a promising animal protein for the development of biodegradable packaging films due to its excellent film-forming ability, good transparency and functional properties.

[0003] Typically, 46% of gelatin comes from pig skin, 29.4% and 23.1% from cow hide and bones, and about 1.5% from fish. Gelatin has a long history of safe use in various fields. It is one of the most versatile biomaterials in the food, cosmetics, pharmaceutical and medical industries due to its advantages such as low cost, abundance, biocompatibility, biodegradability and functionality. In addition, gelatin's special ability to form networks, induce plasticity and increase elasticity is essential for the manufacture of biopolymer films. However, its development in active packaging is limited due to its low antioxidant and antibacterial properties, poor stability, poor water resistance, poor ductility and easy solubility in water. To date, many works have focused on incorporating bioactive compounds into gelatin matrices for active packaging.

[0004] As a green and effective protein modification method, the Maillard reaction changes the structure of proteins. In terms of functional properties, protein-polysaccharide covalent complexes are usually better than single proteins or single polysaccharides. Although many studies have shown that substances produced by improper control of Maillard reaction conditions can reduce the bioavailability of food and increase the risk of cytotoxicity and chronic diseases. However, with the gradual study and mastery of the Maillard reaction, Maillard reaction products with flavor, nutrition and functionality are still the future of the food industry and have broad application prospects in the medical field.

[0005] The extension of the shelf life of food is in line with the current trend of the food packaging industry, which includes the development of active packaging to extend the shelf life of food. Glucose and gelatin are cross-linked through the Maillard reaction to obtain packaging materials with active functions. Cross-linked gelatin composite active films help to improve the shelf life of food, which may be due to the formation of ultraviolet absorbing compounds (secondary antioxidant function) and the antioxidant activity of Maillard products (primary antioxidant function), which can respectively prevent / inhibit the oxidation reaction of lipids in food. However, the mechanical properties of cross-linked gelatin composite active films are not ideal, which limits their practical application. Therefore, improving the mechanical properties and gas barrier properties of cross-linked gelatin composite active films will become the focus of the present invention. Summary of the invention

[0006] The purpose of the present invention is to provide a polyvinyl alcohol reinforced cross-linked gelatin composite active film. The addition of polyvinyl alcohol can improve the thermal stability, gas barrier properties and antioxidant properties of the cross-linked gelatin composite active film, and has high application potential in the field of active packaging.

[0007] Another object of the present invention is to provide a method for preparing a polyvinyl alcohol-reinforced cross-linked gelatin composite active film, which has a simple preparation method and has broad application prospects in the field of food packaging.

[0008] Although the glucose cross-linked gelatin composite film through the Maillard reaction has good activity, its mechanical properties are unsatisfactory. Therefore, the present invention enhances the toughness and oxygen barrier properties of the glucose cross-linked gelatin composite film by adding PVA with high toughness, high transparency and good gas barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0010] Figure 1 UV-visible spectra of cross-linked gelatin composite active films;

[0011] Figure 2 FT-IR spectra of gelatin, PVA and GG-P2.5;

[0012] Figure 3 FT-IR spectra of GG-10 and PVA reinforced cross-linked gelatin composite active films;

[0013] Figure 4This is the UV-visible spectrum of PVA reinforced cross-linked gelatin composite active film;

[0014] Figure 5 To enhance the DPPH free radical scavenging activity of PVA cross-linked gelatin composite active film;

[0015] Figure 6 To enhance the ABST free radical scavenging activity of PVA-crosslinked gelatin composite active films;

[0016] Figure 7 Enhance the oxygen permeability and water vapor permeability of PVA cross-linked gelatin composite active films. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0018] The following is a detailed description of a polyvinyl alcohol reinforced cross-linked gelatin composite active film and a preparation method according to an embodiment of the present invention.

[0019] The embodiment of the present invention provides a polyvinyl alcohol-enhanced cross-linked gelatin composite active film comprising gelatin, glycerol, glucose and polyvinyl alcohol.

[0020] The embodiment of the present invention also provides a method for preparing a polyvinyl alcohol reinforced cross-linked gelatin composite active film, the preparation method comprising the following steps:

[0021] S1, weighing a certain amount of polyvinyl alcohol, adding the polyvinyl alcohol to deionized water to obtain a polyvinyl alcohol solution, heating the polyvinyl alcohol solution and continuously stirring until the polyvinyl alcohol is completely dissolved, and then slowly cooling the solution for standby use;

[0022] S2, adding gelatin, glucose and glycerol to the above polyvinyl alcohol solution, stirring to obtain a uniform film-forming liquid, pouring the film-forming liquid into a horizontally placed mold, drying to obtain a composite active film, and then continuing to heat the dried composite active film to promote glycosylation to obtain the product polyvinyl alcohol enhanced cross-linked gelatin composite active film.

[0023] Furthermore, in a preferred embodiment of the present invention, the concentration of polyvinyl alcohol is 2.5% to 10%.

[0024] Furthermore, in a preferred embodiment of the present invention, the mass ratio of gelatin, glucose and glycerol is 10:1:1.

[0025] Furthermore, in a preferred embodiment of the present invention, in S2, the specific step of stirring is magnetic stirring at 60° C. for 30 min.

[0026] Furthermore, in a preferred embodiment of the present invention, in S2, the specific step of drying is drying at 40° C. for 24 hours.

[0027] Furthermore, in a preferred embodiment of the present invention, in S2, the specific step of heating is heating at 105°C for 24 hours.

[0028] Furthermore, in a preferred embodiment of the present invention, the optimal volume of the deionized water is 20 mL.

[0029] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0030] Example 1

[0031] Table 1 Materials and reagents used in this experiment

[0032]

[0033]

[0034] Preparation of polyvinyl alcohol reinforced cross-linked gelatin composite active film

[0035] As shown in Table 2, a certain amount of PVA powder (2.5%, 5%, 7.5%, 10%, based on the dry weight of gelatin) was weighed, and PVA was added to 20 mL of deionized water, then heated and stirred continuously until the PVA was completely dissolved, and then slowly cooled to 60°C for standby use. 1.25 g of gelatin, 0.125 g of glucose (10%, based on the dry weight of gelatin), and 0.125 g of glycerol were added to the above PVA solution, and magnetic stirring was continued at 60°C for 30 minutes to obtain a uniform film-forming liquid. The film-forming liquid was poured into a horizontally placed mold, dried at 40°C for 24 hours, and then the dried composite active film was continued to be heated at 105°C for 24 hours to promote glycosylation.

[0036] Table 2 Nomenclature and composition of PVA-enhanced cross-linked gelatin composite active films

[0037]

[0038] Comparative Example 1

[0039] Preparation of cross-linked gelatin composite active film

[0040] The cross-linked gelatin composite film was prepared by casting film (the material ratio is shown in Table 2). 1.25g of gelatin, a certain proportion of glucose, and 0.125g of glycerol were added to 20mL of deionized water, and magnetically stirred at 60°C for a certain period of time to obtain a uniformly mixed gelatin casting solution (ultrasound is required to reduce bubbles). Among them, the amount of glucose (based on the dry weight of gelatin) was 5%, 7.5%, 10%, and 12.5%, respectively. The gelatin casting solution was poured into a horizontally placed mold, dried at 40°C for 24h, and then the dried gelatin composite film was heated at 105°C for 24h to promote glycosylation. Among them, NGG-0 and NGG-10 are films that have not been subjected to the Maillard reaction at 105°C. After the reaction, the cross-linked gelatin composite film was placed at 23°C and 50RH (humidity) for 48h before testing.

[0041] Table 3 Nomenclature and composition of cross-linked gelatin composite active films

[0042]

[0043] Results and Discussion

[0044] Characterization of cross-linked gelatin composite active films

[0045] Analysis of Optical Properties of Cross-linked Gelatin Composite Active Films

[0046] The UV-visible light barrier property of the film is a good barrier to prevent UV-visible light-induced lipid oxidation in food, which can maintain the sensory properties of packaged food and effectively extend the shelf life of food. Figure 1 As shown in Table 4, compared with the UV-visible light transmittance of gelatin films without Maillard reaction, the transmittance of cross-linked gelatin composite active films with 5%, 7.5%, 10% and 12.5% ​​glucose added was reduced. This is because glucose and gelatin underwent Maillard reaction at 105°C to generate Maillard products (MRPs). Along with the occurrence of the Maillard reaction, the cross-linked gelatin composite active film browned, causing the transmittance to decrease. The transmittance, thickness, absorbance at 600nm and opacity of gelatin films and cross-linked gelatin composite active films at different wavelengths are shown in Table 4. By comparing NGG-0 and GG-0, it can be found that the transmittance of GG-0 after the Maillard reaction at 105°C is significantly reduced at wave numbers of 240 to 300nm. This is precisely because the film browned along with the Maillard reaction. It can be found from Table 4 that the transmittance of GG-5 and GG-10 at 280nm, 294nm and 315nm is zero. Figure 1It can also be observed that in the visible light range of 400-500 nm, the transmittance of GG-7.5, GG-10 and GG-12.5 is relatively low, indicating that glucose and gelatin are well cross-linked.

[0047] By monitoring the transmittance at different wavelengths, the absorbance at 600nm and the opacity of the film, it can be roughly determined that when 10% glucose is added, the cross-linking reaction between glucose and gelatin is better. As shown in Table 4, the transmittance of GG-10 at 420nm and 500nm is lower than that of the cross-linked gelatin composite active film with 0%, 5%, 7.5% and 12.5% ​​glucose, which are 1.9% and 5.1% respectively. This is because there will be a large amount of brown polymer melanoidin in the later stage of the Maillard reaction. As the reaction time increases, the amount of pigment substances will increase and the degree of browning will deepen. Compared with the opacity of GG-0, GG-10 has increased by 68.7%.

[0048] Table 4 Optical properties of cross-linked gelatin composite active films

[0049]

[0050] Water resistance analysis

[0051] The test results of water resistance of cross-linked gelatin composite active film are shown in Table 5. From the data in Table 5, it can be found that the water absorption rate, swelling rate and water solubility of cross-linked gelatin composite active film after Maillard reaction are lower than those of glucose gelatin film without Maillard reaction. This may be due to the fact that hydrogen bonds, electrostatic interactions and hydrophobic interactions within protein molecules after Maillard reaction will expose the hydrophobic groups inside the protein and cover the surrounding hydrophilic groups, thereby increasing the surface hydrophobicity of the protein. Compared with GG-0, the water absorption rate, swelling rate and water solubility of GG-5 decreased by 84%, 70.2% and 66.9%, respectively. When the amount of glucose added reached 10%, the swelling rate and water solubility were the lowest, which were 278.6% and 23.0%, respectively. This also shows that when 10% glucose was added, the cross-linking reaction between glucose and gelatin was better, and the water resistance of cross-linked gelatin composite active film was significantly improved. Therefore, 10% glucose addition was selected as the optimal ratio in the later stage of the experiment. When 12.5% ​​glucose was added, the water solubility and swelling rate increased, which may be due to the introduction of hydrophilic carbonyl groups by the addition of a large amount of polysaccharides, which caused a certain degree of "masking" on the protein surface, that is, the protein surface was covered by hydrophilic polysaccharide chains. In addition, the exposure of some hydrophilic groups of the protein will also increase the hydrophilicity, thereby showing a decrease in surface hydrophobicity.

[0052] Table 5 Water resistance test results of cross-linked gelatin composite active film

[0053]

[0054] Characterization of PVA-reinforced cross-linked gelatin composite active films

[0055] Chemical structure analysis

[0056] FT-IR spectra of gelatin, PVA and GG-P2.5, such as Figure 2 As shown in Figure 2, the FT-IR spectra of the cross-linked gelatin composite active film and the PVA-enhanced cross-linked gelatin composite active film are as follows: Figure 3 In the infrared spectrum of PVA, 3284cm -1 The strong absorption peak at 2940 cm is the stretching vibration peak of -OH. -1 The stretching vibration absorption peak of -CH2 is 1036cm -1 The peak at 1644cm is the stretching vibration peak of CO. -1 、1528cm -1 The absorption peaks at the positions are the amide I and II peaks of proteins. In the infrared spectrum of GG-P2.5 film, the amide I and II peaks shifted to 1631 cm -1 and 1530cm -1 This indicates that the amino groups of gelatin in the blend film interact strongly with the hydroxyl groups in the PVA molecules. -1 and 1036cm -1 The stretching vibration peak at 27° becomes narrower and moves to a higher wave number. Therefore, there may be strong interactions such as hydrogen bonds between PVA and gelatin molecules, which reduces the Gibbs free energy of the blending system and enhances the compatibility between the components in the blending system.

[0057] UV-visible spectra of NGG-0, GG-10 and PVA reinforced cross-linked gelatin composite active films are shown in Figure 2. Figure 4As shown. Among them, the pure NGG-0 film has the highest UV-visible light transmittance. In the ultraviolet light range (200-400nm), the transmittance of the cross-linked gelatin composite active film is lower than that of the PVA enhanced cross-linked gelatin composite active film, and with the increase of the added PVA content, the transmittance of the cross-linked gelatin composite active film increases successively. Taking the ultraviolet wavelength of 380nm as an example, when the PVA content reaches 2.5%, the ultraviolet transmittance of GG-P2.5 and GG-P10 has no significant change compared with GG-10. In the visible light range (400-780nm), with the increase of PVA concentration, the transmittance of PVA enhanced cross-linked gelatin composite active film also increases. Taking the wavelength of 550nm as an example, compared with GG-10, when the PVA addition reaches 2.5%, the transmittance of PVA enhanced cross-linked gelatin composite active film has no significant change. When the PVA addition reaches 10%, the PVA enhanced cross-linked gelatin composite active film increases by 34.6%. It can be seen that the light absorption capacity of PVA-enhanced cross-linked gelatin composite active film under ultraviolet light is significantly stronger than that under visible light. In addition, by comparing the transmittance of GG-10 and GG-P10, it can be found that the cross-linking effect of glucose and gelatin is the main source of the ultraviolet-visible light barrier performance of the cross-linked gelatin composite active film. Since PVA has a large ultraviolet-visible light transmittance, the transmittance of the cross-linked gelatin composite film gradually increases with the increase of PVA content. Therefore, we need to find a suitable amount of PVA added to prevent the ultraviolet-visible light transmittance from being too high, which affects the use of PVA-enhanced cross-linked gelatin composite active film.

[0058] Mechanical properties analysis

[0059] The mechanical properties of PVA-enhanced cross-linked gelatin composite active films are shown in Table 7. By comparing the elongation at break of GG-10 and PVA-enhanced cross-linked gelatin composite active films, it can be found that the elongation at break of 2.5% and 5% PVA cross-linked gelatin composite active films increased by 18.1% and 76.7%, respectively, indicating that the addition of PVA can significantly enhance the toughness of the cross-linked gelatin composite active film. This is because the main molecular chain of PVA is a straight chain with a planar zigzag structure and a relatively flexible molecular chain. However, with the increase of elongation at break, the tensile strength and breaking force also decreased significantly, so it is crucial to find a suitable amount of PVA added.

[0060] Table 7 Elongation at break, tensile strength and breaking force of PVA-reinforced cross-linked gelatin composite active films

[0061]

[0062] Antioxidant performance analysis

[0063] DPPH radical scavenging activity of PVA-enhanced cross-linked gelatin composite active films Figure 5 As shown above, it is mentioned that gelatin itself has poor antioxidant properties. Figure 5 It can also be seen that the antioxidant activity of NGG-10 is 0. This may be because the film was broken during the stirring process, and the film fragments entered the cuvette during UV exposure. After the Maillard reaction at 105°C, the antioxidant activity of the cross-linked gelatin composite active film increased. For example, the antioxidant activity of GG-10 increased by 33.8% compared with NGG-10. This is because the Maillard reaction will generate MRPs with antioxidant properties such as melanoidins and reductones. As the amount of PVA added increases, the antioxidant activity of the cross-linked gelatin composite active film increases. This is because PVA contains hydroxyl groups (-OH), which will cross-link with proteins in gelatin, thereby changing the structure of the protein and improving the antioxidant activity of the cross-linked gelatin composite active film. The antioxidant properties of the cross-linked gelatin composite active film with 5% and 7.5% PVA added were increased to 71.6% and 60.2%, respectively. It can also be seen from the figure that the antioxidant property of GG-P10 was reduced to 14.2%. This may be due to the uneven oven temperature, which caused the Maillard reaction of some films to enter the advanced stage, thereby causing the antioxidant melanoidin and reductone to decompose, resulting in a decrease in the antioxidant property of the cross-linked gelatin composite active film. Therefore, the oven temperature must be controlled when preparing the film. Too high or too low a temperature will affect the occurrence of the Maillard reaction. Figure 5 The color change of the solution can also be used to observe the changing trend of its antioxidant activity.

[0064] ABST free radical scavenging activity of PVA-reinforced cross-linked gelatin composite active films Figure 6As shown in the figure, after the Maillard reaction, the ABST free radical scavenging activity of the film increases, which is also due to the generation of MRPs. With the increase of PVA content, the ABST free radical scavenging activity of the film also tends to increase, among which GG-P2.5 and GG-P7.5 are 28.0% and 17.3% higher than GG-10, respectively. This is because PVA contains hydroxyl (-OH), which can react with amino acid residues (especially lysine and lysine) in proteins to form a cross-linked structure. After PVA and protein are cross-linked, a stable complex can be formed, thereby enhancing the stability and antioxidant properties of the protein. In addition, PVA itself has certain antioxidant properties, which can capture free radicals and stabilize oxidation reactions. Therefore, after PVA is cross-linked with protein, the antioxidant capacity of the complex can be improved, thereby protecting the protein from free radical oxidation damage and improving its antioxidant properties. The antioxidant activity of GG-P10 was 28.3% lower than that of GG-P7.5. This may be because the Maillard reaction of some films entered an advanced stage due to various uncontrollable factors such as uneven temperature in different parts of the oven during the Maillard reaction, which caused the antioxidant MRPs to decompose under heat, thus reducing the antioxidant activity of the film. Figure 6 The color change of the solution in the glass bottle can also be used to observe the changing trend of its antioxidant properties.

[0065] Barrier performance analysis

[0066] The barrier property of a film refers to the permeability of the film to substances such as gases, water vapor, and organic matter. Generally speaking, the better the barrier property of a film, the lower its permeability to substances such as gases, water vapor, and organic matter. The barrier property of a film is determined by the characteristics of its material, such as molecular structure, molecular weight, crystallinity, melting point, glass transition temperature, hydrophilicity, and hydrophobicity. The barrier property of a film is very important for active packaging materials because it directly affects the protective effect of the packaging material on products such as food and medicine. For example, the better the barrier property of a food packaging film, the more it can prevent the penetration of substances such as oxidation, moisture, and odor, thereby extending the shelf life and quality of the food. Therefore, the barrier property of a film is one of the factors that need to be considered in the design and application of film materials.

[0067] Oxygen permeability (OTR) and water vapor permeability (WVTR) are performance indicators used to evaluate the oxygen and water vapor permeability of films, respectively. Oxygen permeability reflects the film's barrier capacity to oxygen, while water vapor permeability reflects the film's barrier capacity to water vapor. Figure 7 ,from Figure 7It can be seen that with the increase of PVA addition, the oxygen permeability decreases. This is because gelatin reacts with the hydroxyl groups in the PVA molecules to form a cross-linked structure. The structure of the PVA-enhanced cross-linked gelatin composite active film becomes tighter, making the distance between molecules in the film smaller, thereby lengthening the diffusion path of oxygen molecules in the film and making it difficult to pass through the film. Compared with GG-10, the oxygen permeability of GG-P2.5 and GG-P5 decreased by 30.04% and 47.91%, respectively. On the contrary, with the increase of PVA addition, the water vapor permeability increases. This is because PVA contains water-absorbing groups hydroxyl groups (-OH), which promotes the permeation of water vapor into the film. Compared with GG-10, the water vapor permeability of GG-P2.5 and GG-P5 increased by 18.87% and 27.36%, respectively. Therefore, the addition of PVA will enhance the barrier properties of the PVA cross-linked gelatin composite active film, but it will also reduce the barrier properties to a certain extent. Therefore, when enhancing the cross-linked gelatin composite active film, it is necessary to select an appropriate amount of PVA addition.

[0068] in conclusion

[0069] The embodiment of the present invention uses the Maillard reaction of protein and polysaccharide to give the film a certain activity, and improves its mechanical properties and oxygen barrier properties by adding PVA. First, the ratio of glucose cross-linked gelatin composite active film is determined, and the appropriate ratio is determined by measuring its optical properties and water resistance, and then on this basis, the effects of different proportions of PVA on its mechanical properties, water resistance, antioxidant properties and thermal stability are explored.

[0070] (1) The chemical structure of the cross-linked gelatin composite active film was analyzed by FT-IR, and the microscopic morphology of the film surface was further observed by high-magnification SEM. The results showed that strong interactions, such as hydrogen bonds, may have formed between PVA and gelatin molecules, so the Gibbs free energy of the blending system was reduced and the compatibility between the components was improved. The existence of this interaction made it easier for PVA and gelatin molecules to mix together, reducing the mutual repulsion between them, thereby improving the stability and physical properties of the blended film.

[0071] (2) The optical properties of the cross-linked gelatin composite active film were studied using a spectrophotometer and UV-Vis spectroscopy. The results showed that as the Maillard reaction occurred, the cross-linked gelatin composite active film browned, which increased the opacity of the film. Compared with the film without Maillard reaction, the UV-visible light transmittance decreased, that is, the anti-ultraviolet light performance was improved. After adding PVA, the UV-visible light transmittance of the film increased and the opacity of the film decreased. When the PVA addition amount reached 10%, the transmittance of the PVA-enhanced cross-linked gelatin composite active film increased by 34.6% compared with GG-10.

[0072] (3) The mechanical properties test results of PVA-enhanced cross-linked gelatin composite active film showed that the elongation at break of the cross-linked gelatin composite active film with 5% PVA added increased by 76.7% compared with GG-10, which indicates that the appropriate amount of PVA added can significantly improve the toughness of the cross-linked gelatin composite active film.

[0073] (4) The antioxidant test results of the cross-linked gelatin composite active film showed that the antioxidant properties of the film after the Maillard reaction were improved, and the antioxidant properties of the film were also significantly enhanced after the addition of PVA. Compared with GG-10, the cross-linked gelatin composite active film with the addition of 5% and 7.5% PVA increased the scavenging ability of DPPH free radicals by 37.8% and 26.4%, respectively. The cross-linked gelatin composite active film with the addition of 2.5% and 7.5% PVA increased the scavenging ability of ABTS free radicals by 28.0% and 17.3%, respectively. The antioxidant test results showed that the presence of PVA did not reduce the content of active ingredients, but instead promoted the release of active substances.

[0074] (5) The barrier performance test results of the cross-linked gelatin composite active film show that with the increase of PVA addition, the oxygen permeability decreases. Compared with GG-10, the oxygen permeability of GG-P2.5 and GG-P5 decreases by 30.04% and 47.91%, respectively. With the increase of PVA addition, the water vapor permeability increases. Compared with GG-10, the water vapor permeability of GG-P2.5 and GG-P5 increases by 18.87% and 27.36%, respectively. This reflects that the effect of PVA on the oxygen barrier performance of the cross-linked gelatin composite active film is significantly higher than that on the water vapor barrier performance.

[0075] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A polyvinyl alcohol reinforced cross-linked gelatin composite active film, characterized in that: The polyvinyl alcohol-enhanced cross-linked gelatin composite active film comprises gelatin, glycerol, glucose, and polyvinyl alcohol; and the preparation method of the polyvinyl alcohol-enhanced cross-linked gelatin composite active film comprises the following steps: S1, weighing a certain amount of polyvinyl alcohol, adding the polyvinyl alcohol to deionized water to obtain a polyvinyl alcohol solution, heating the polyvinyl alcohol solution and continuously stirring until the polyvinyl alcohol is completely dissolved, and then slowly cooling the solution for standby use; S2, adding gelatin, glucose and glycerol to the above polyvinyl alcohol solution, stirring to obtain a uniform film-forming liquid, pouring the film-forming liquid into a horizontally placed mold, drying to obtain a composite active film, and then continuing to heat the dried composite active film to promote glycosylation to obtain the product polyvinyl alcohol enhanced cross-linked gelatin composite active film.

2. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: The concentration of the polyvinyl alcohol is 2.5% to 10%.

3. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: The mass ratio of the gelatin, glucose and glycerol is 10:1:

1.

4. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: In S2, the specific step of stirring is magnetic stirring at 60° C. for 30 min.

5. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: In S2, the specific step of drying is drying at 40° C. for 24 hours.

6. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: In S2, the specific step of heating is heating at 105° C. for 24 hours.

7. The polyvinyl alcohol reinforced cross-linked gelatin composite active film according to claim 1, characterized in that: The optimal volume of the deionized water is 20 mL.